Influence Of Fabrication Condition on the Microstructural and Optical Properties of Lead-Free Ferroelectric Bi\(_0.5\)Na\(_0.5\)TiO\(_3\) Materials - Thanh, Le Thi Hai; Tuan, Nguyen Hoang; Bac, Luong Huu; Dung, Dang Duc; Bao, Phung Quoc (Communications in Physics, 2016)
Lead-free ferroelectric materials have attracted considerable attention due to the increasing potential application in environmental benign materials. Among lead-free ferroelectric materials, the Bi0.5Na0.5TiO3 (BNT) materials were more studied because it exhibited the good ferroelectric and piezoelectric properties which could be promising candidate materials replacing Pb(Zr,Ti)O3. In this work, the lead-free ferroelectric BNT materials were synthesized by sol-gel method. The effects of fabrication process to microstructural and optical properties were studied which includes Na precursor concentration and calcining temperature. The result indicated that the Na precursor concentration were higher 40 mol.% and the calcining temperatures